CMIP5 Intermodel Relationships in the Baseline Southern Ocean Climate System and With Future Projections - Jules B. Kajtar (Earth's Future, 2021)
Abstract Climate models exhibit a broad range in the simulated properties of the climate system. In the early historical period, the absolute global mean surface air temperature in Coupled Model Intercomparison Project, Phase 5 (CMIP5) models spans a range of ∼12°C – 15°C. Other climate variables may be linked to global mean temperature, and so accurate representation of the baseline climate state is crucial for meaningful future climate projections. In CMIP5 baseline climate states, statistically significant intermodel correlations between Southern Ocean surface temperature, outgoing shortwave radiation, cloudiness, the position of the mid‐latitude eddy‐driven jet, and Antarctic sea ice area are found. The baseline temperature relationships extend to projected future changes in the same set of variables, impacting on the projected global mean surface temperature change. Models with initially cooler Southern Ocean tend to exhibit more global warming, and vice versa for initially warmer models. These relationships arise due to a “capacity for change”. For example, cold‐biased models tend to have more cloud cover, sea ice, and equatorward jet initially, and thus a greater capacity to lose cloud cover and sea ice, and for the jet to shift poleward under global warming. A first look at emerging data from CMIP6 reveals a shift of the relationship from the Southern Ocean towards the Antarctic region, possibly due to reductions in Southern Ocean biases, such as in westerly wind representation.